Community nurse practitioner’s roles on smoking cessation assistance for patients with non-communicable disease - Ruamsook, Tanawat; Lumrod, Nichamon; Likitpongwit, Boontip (Thai Journal of Nursing, 2021)
Smoking is a major risk factor for patients with non-communicable disease. Especially, patients with hypertension and diabetes mellitus whose could raise the severity of high blood pressure, high blood sugar level and could lead to disability and death. The objective of this article is to propose a quit smoking guideline for patients with non-communicable disease in primary care, secondary care and tertiary care regarding community nurse practitioner roles. This guideline application can reduce severity and complications of those non-communicable diseases. Then, a better quality of life among patients with non-communicable disease can be promoted.